Guinea-Bissau : First and Second Reviews Under the Extended Credit Facility Arrangement, Request for Rephasing of Disbursements, Modification of Performance Criteria and Financing Assurances Review-Press Release; Staff Report; and Statement by the Executive Director for Guinea-Bissau. (IMF Staff Country Reports; Country Report, 2016)
This paper discusses Guinea-Bissau's First and Second Reviews Under the Extended Credit Facility (ECF) arrangement, Request for Rephasing of Disbursements, Modification of Performance Criteria, and Financing Assurances Review. All performance criteria for the first and second reviews were met. The IMF staff discussions with the authorities focused on measures to fill the 2016 financing gap that resulted from the loss of budget support and steps to reignite structural reforms. The authorities undertook remedial measures, including declaring the bank bailout operation null and void and measures to address weaknesses in public financial management. The IMF staff supports completion of the first and second reviews under the ECF arrangement and the authorities' requests for modification of performance criteria and rephasing of disbursements.